2021
DOI: 10.1186/s12284-021-00469-w
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning Roles of Osa-miR159a in Rice Immunity Against Magnaporthe oryzae and Development

Abstract: Background Rice blast caused by Magnaporthe oryzae is one of the most destructive diseases of rice. An increasing number of microRNAs (miRNAs) have been reported to fine-tune rice immunity against M. oryzae and coordinate with growth and development. Results Here, we showed that rice microRNA159a (Osa-miR159a) played a positive role in rice resistance to M. oryzae. The expression of Osa-miR159a was suppressed in a susceptible accession at 12, 24, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…However, lre-miR159a slightly changed in susceptible cultivar during the infection period, except for a significant increase at 12 hpi [ 40 , 41 ]. In rice infected with Magnaporthe oryzae , the expression of Osa-miR159a reduced in a susceptible cultivar at 12, 24 and 48 hpi, while it was increased in a resistant cultivar at 24 hpi [ 42 ]. In our study, the expression level of soybean miR159 decreased in response to H. glycines , especially at 10 and 15 dpi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lre-miR159a slightly changed in susceptible cultivar during the infection period, except for a significant increase at 12 hpi [ 40 , 41 ]. In rice infected with Magnaporthe oryzae , the expression of Osa-miR159a reduced in a susceptible cultivar at 12, 24 and 48 hpi, while it was increased in a resistant cultivar at 24 hpi [ 42 ]. In our study, the expression level of soybean miR159 decreased in response to H. glycines , especially at 10 and 15 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, according to the positions of the six GAMYB genes in the phylogenetic tree ( Supplementary Figure S3 ), a closer evolutionary relationship was observed with AtMYB33 ; therefore, they are renamed GmMYB33 a/b/c/d/e/f in our study ( Supplementary Figure S3 ). GAMYB genes were reported to function as immunity regulators in several plants such as rice [ 42 ] and Arabidopsis [ 49 ]. However, transcriptome analyses showed that soybean MYB genes expressed differently in both SCN resistance and susceptible cultivars [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, more than 15 miRNAs have been characterized as the regulators of rice blast disease resistance. miR159 (Chen et al 2021 ), miR160 (Li et al 2014 ), miR162 (Salvador-Guirao et al 2019 ; Li et al 2020 ), miR166 (Salvador-Guirao et al 2018 ), miR398 (Li et al 2019 ), miR7695 (Campo et al 2013 ), and miR812w (Campo et al 2021 ) positively regulate rice resistance against M. oryzae , whereas miR156 (Zhang et al 2020 ), miR164 (Wang et al 2018b ), miR167 (Zhao et al 2019b ), miR169 (Li et al 2017 ), miR319 (Zhang et al 2018 ), miR396 (Chandran et al 2019 ), miR439 (Lu et al 2021 ), miR444b.2 (Xiao et al 2017 ), and miR1873 (Zhou et al 2020 ) negatively regulate rice disease resistance. Among these miRNAs, some and their target genes are involved in both rice immunity and growth.…”
Section: Introductionmentioning
confidence: 99%
“…MiR159a is a positive regulator of resistance to Magnaporthe oryzae ( M. oryzae ) by targeting OsGAMYB , OsGAMYBL , and OsZF . STTM159a lines showed enhanced susceptibility ( Chen et al, 2021b ). MiR162b, miR166, and miR535 were confirmed to participate in the response to drought stress.…”
Section: Application Of the Sttm Technique For Rice Functional Genomics And Breedingmentioning
confidence: 99%